Areas and Perspectives of the World Wine Market - Passaro, Pierluigi (European Scientific Journal, ESJ, 2019)
This paper focuses on offering a synthetic picture of the areas and perspectives of the world wine market as observed in its international dimension. In the last thirty years, important changes have succeeded in quantitative terms as a result of qualitative expectations from the public and market structure. Henceforth, the different actors must restructure their strategies and behaviours. Apparently, the wine sector will be able to see a sensitive concentration process among companies positioned at the lower market segments. There is a situation in which a relatively reduced number of large companies dominates this part of the market. It exploits some key success factors, which is a range of offers based on several brands of international fame, eventually with a strong territorial connotation. It is assigned to specific public segments, economies of scale, and a capillary distribution optimized with respect to costs. Though the different companies categories appear in competition in the wine market, nonetheless, they are allies in the crucial battle for the support and development of wine consumption. This, as we have already seen, competes in a now definitely saturated beverage market. The consumption of wine, in particular, appears threatened by a difficulty in approaching young people for its daily consumption in traditional consumer countries. There is amassive anti-alcohol campaign in many countries in addition to the encourged position of theWorld Health Organization that tends to become increasingly hostile to alcohol and in which wine is put on the same level as all the other alcoholic beverages